Effective Knockdown of Gene Expression in Primary Microglia With siRNA and Magnetic Nanoparticles Without Cell Death or Inflammation - Carrillo-Jimenez, Alejandro; Puigdellívol, Mar; Vilalta, Anna; Venero, Jose Luis; Brown, Guy Charles; StGeorge-Hyslop, Peter; Burguillos, Miguel Angel (Frontiers in Cellular Neuroscience, 2018)
Microglia, the resident immune cells of the brain, have multiple functions in physiological and pathological conditions, including Alzheimer’s disease (AD). The use of primary microglial cell cultures has proved to be a valuable tool to study microglial biology under various conditions. However, more advanced transfection methodologies for primary cultured microglia are still needed, as current methodologies provide low transfection efficiency and induce cell death and/or inflammatory activation of the microglia. Here, we describe an easy, and effective method based on the Glial-Mag method (OZ Biosciences) using magnetic nanoparticles and a magnet to successfully transfect primary microglia cells with different siRNAs. This method does not require specialist facilities or specific training and does not induce cell toxicity or inflammatory activation. We demonstrate that this protocol successfully decreases the expression of two key genes associated with Alzheimer’s disease, the triggering receptor expressed in myeloid cells 2 (TREM2) and CD33, in primary microglia cell cultures.